Correlation of equine sperm kinetic parameters with fertility index - Trinque, Camila Moreira [UNESP]; Silva, Luan Sitó [UNESP]; Pereira, Raiza Rocha [UNESP]; Canuto, Lucas Emanuel Ferreira [UNESP]; Cavalero, Thaís Mendes Sanches [UNESP]; de Paula Freitas-Dell'Aqua, Camila [UNESP]; Papa, Frederico Ozanam [UNESP] (Elsevier, 2023)
In horses, fertility has a great economic impact on reproductive management and several studies have been carried out in order to optimize the success rate of reproductive biotechnologies. For stallions, reliable prediction of fertility by semen evaluation is therefore required, such as kinetics, membrane integrity and morphology. Analysis of total sperm motility is one of the most important characteristics assessed in horse semen worldwide. With the aim to reduce the subjectivity of this method, computerized seminal analysis systems (CASA) was introduced. Even with more sophisticated motility assessments, however, CASA cannot accurately predict semen sample fertility (Amann et al., 2014). The objective of this work was to retrospectively analyze the correlation between kinetic parameters such as total motility (TM), progressive motility (PM) and rapid spermatozoa (RAP) of stallions and their fertility rates. We analyzed 22 publications, theses and dissertations from the Center for Biotechnology and Animal Reproduction (CERAN)- UNESP, Botucatu, São Paulo, published between 2008 and 2017. The works provided data on kinetic parameters, MT, MP and RAP, (VAP >70 μm/s and STR >80%) by computerized analysis CASA (Hamilton Thorn Research – IVOS ® 12, Beverly, Massachusetts, USA) of refrigerated and frozen semen from approximately 44 stallions,together with information on their in vivo fertility by insemination of mares (N=372) under different managements conditions. For statistical analysis, Spearman's determination test and correlation coefficient were used (software GraphPad). In average, 3.4±3.2 stallions were used with 16.9±6.1 mares per publication. MT was 60.2±17.9%, MP 26.9±11.5%, and RAP 48.2±16.7%, respectively. The average fertility in the studies was 52.1±25.9%. Fertility rate was determined per cycle, with ultrasound performed 15 days after insemination. A strong correlation was found for fast spermatozoa with fertility rate (r = 0.74; p<0.0001) and moderate correlations for PM and TM (r = 0.61 and 0.53; p<0.01, respectively) as well as TM, PM and RAP, (R2= 0.37; R2=0.42; R2= 0.46; respectively) and p<0.01. This retrospective study demonstrates that the three parameters TM, PM and RAP are positively correlated and RAP had the greatest association with fertility. In conclusion, among the analyzed variables, RAP is most consistent with the fertility of stallion semen. Acknowledgements: The authors are grateful to Coordenação de Aperfeiçoamento de Pessoal de Nível Superior – (CAPES).